Development of all solid-state ultrafast lasers and optical fibre soliton lasers - Chin, Mee Koy. (2008)
The primary objective of this project was to establish a programme to investigate ultrashort pulse formation in laser gain media and optical fibres with the latest technique, and the physics of the pulse-shortening and nonlinear interaction between the optical wave packets and optical materials.